1972
DOI: 10.3109/00016347209154016
|View full text |Cite
|
Sign up to set email alerts
|

The Distribution of 125I‐Marked Bovine Prolactin and Human Chorionic Gonadotrophin in Rats with Experimental Ovarian Tumours

Abstract: The distribution and fate of 1251-labelled bovine prolactin, human chorionic gonadotrophin and bovine serum albumin was studied and followed by serial gamma camera photographs, scintillation counting of blood and tissues, and autoradiography in normal pro-oestrus rats, in oophorectomized rats and in rats with experimental ovarian tumours developed in intrasplenic ovarian grafts after bilateral oophorectomy. A high affinity for T -H C G was found both in ovarian tumours and in normal ovaries. An increased activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1974
1974
1992
1992

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…injection of 125I-labelled protein hormones into animals or by the incubation of the target organ with the labelled hormone. Human chorionic gonadotrophin (HCG) (Eshkol & Lunenfeld, 1968;Carlsson, Kullander & Müller, 1972;Catt, Tsuruhara & Dufau, 1972;Danzo, Midgley & Kleinsmith, 1972;Leidenberger & Reichert, 1972;Yaginuma, 1972), prolactin (Birkinshaw & Falconer, 1972;Shani (Mishkinsky), Givant, Sulman, Eshkol & Lunenfeld, 1972) and luteinizing hormone (LH) (Barofsky, Lipner & Armstrong, 1971) iodinated by the standard chloramine-T method, all retained sufficient biological activity to be taken up and bound to target receptors. Recently, Moodbidri, Sheth & Rao (1973) have shown that HPL radioiodinated by the modified method of Greenwood et al (1963) was bound to membranes of the buffalo corpus luteum.…”
Section: Discussionmentioning
confidence: 97%
“…injection of 125I-labelled protein hormones into animals or by the incubation of the target organ with the labelled hormone. Human chorionic gonadotrophin (HCG) (Eshkol & Lunenfeld, 1968;Carlsson, Kullander & Müller, 1972;Catt, Tsuruhara & Dufau, 1972;Danzo, Midgley & Kleinsmith, 1972;Leidenberger & Reichert, 1972;Yaginuma, 1972), prolactin (Birkinshaw & Falconer, 1972;Shani (Mishkinsky), Givant, Sulman, Eshkol & Lunenfeld, 1972) and luteinizing hormone (LH) (Barofsky, Lipner & Armstrong, 1971) iodinated by the standard chloramine-T method, all retained sufficient biological activity to be taken up and bound to target receptors. Recently, Moodbidri, Sheth & Rao (1973) have shown that HPL radioiodinated by the modified method of Greenwood et al (1963) was bound to membranes of the buffalo corpus luteum.…”
Section: Discussionmentioning
confidence: 97%
“…The majority of ovarian cancers are of epithelial origin. A similar dependency on gonadotropins may occur in certain human ovarian tumors (125)(126)(127). Most common functioning ovarian neoplasms are referred to as granulosa-theca cell tumors (121,122).…”
Section: Ovarian Cancer and Neoplasms Of The Female Genital Tractmentioning
confidence: 89%
“…Ovarian cancer is not a single entity, but encompasses numerous cell types ( 12 1 ). Animal models of granulosa cell tumors are dependent on hypophyseal gonadotropins for stimulation of hormone secretion, and concentrate '251-labeled HCG (125)(126)(127). The primary treatment of ovarian cancer is surgical removal ( 12 l), but chemotherapy is more commonly used today in the management of disseminated ovarian carcinoma because of unsatisfactory results following operation alone ( 12 1).…”
Section: Ovarian Cancer and Neoplasms Of The Female Genital Tractmentioning
confidence: 99%
“…One possibility to explore the possible target organs as well as the sites of metabolic inactivation and/or excretion is to use auto radiographic techniques with labeled hormone. In a recent study, gamma camera and autoradiography have indicated that 125I-prolactin shows only a slight accumulation in the ovary or splenic ovarian tumors [Carlsson et al, 1972], We have chosen a similar approach using whole-body and microautoradiographic techniques to evaluate the distribution and time-course of disappearance of labeled prolactin in normal cyclic, pregnant and lactating female mice as well as in organs of normal male mice and rats.…”
Section: Introductionmentioning
confidence: 99%